Biophysical and Subject-Based Assessment of the Effects of Topical Moisturizer Usage on Xerotic Skin—Part II: Visioscan® VC 20plus Imaging - Stettler, Hans; Crowther, Jonathan; Boxshall, Alison; Bielfeldt, Stephan; Lu, Bailu; de Salvo, Raffaella; Trapp, Sonja; Blenkiron, Peter (Cosmetics (Basel), 2022)
As new biophysical methods become available to the skin researcher it is important to understand the type of information that they are capable of measuring, and how it relates to consumer perception of topical moisturizing products. The aim of the work presented here was to understand what dry skin imaging can reveal about the skin and subject feedback from the use of a topical moisturizing product and how it relates to the consumer usage experience of a topical product. Images from a dry skin camera—the Visioscan® VC 20plus—during 3 weeks in vivo usage of a topical moisturizing product were analyzed. Subject feedback regarding their skin condition was also collected. Strong statistical improvements (p < 0.05) were observed for a wide range of skin parameters derived from the Visioscan® VC 20plus. Skin scaliness and smoothness and parameters associated with skin health and appearance (surface, energy, contrast, homogeneity) improved as a result of topical product usage. Subjects reported their skin to feel less dry, to be smoother, and more supple and to look and feel healthier after product usage. The length of time until they felt the need to re-apply the product increased during the study.